TECHOLOGIES OF THE IMAGINATION - Stevenson, Michael; Ankerson, Megan Sapnar; Gehl, Robert; Murray, Sarah (AoIR Selected Papers of Internet Research, 2015)
Beginning with narratives of empowerment through personal computing and the ostensibly borderless nature of cyberspace, the imagination of digital media has long held popular appeal. The 1990s fascination with the distinction between the virtual and the real may have subsided, but new imaginaries that seem to capture the character and promise of digital media continue to find their way into hyperbolic news headlines. The social graph, the quantified self and other abstract notions evoke a technological present that was previously impossible. Such widely-publicized imaginations have been routinely criticized: from the early 1990s, various scholars cautioned against the transcendentalism, political naiveté and escapism that pervaded much of the utopian rhetoric around digital media. Like digital utopianism itself, such criticism has hardly slowed down, as evidenced for example by the success of reformed cyberutopians Evgeny Morozov and Jaron Lanier. What goes missing during the back-and-forth between digital utopians and their debunkers, though, is the more general importance of imagination to our experience of new media: it is not (just) the utopian and transcendental associations of digital technology that is worthy of study and critique, but the interplay of materiality and abstraction that occurs at a variety of levels and registers in digital culture. In their own ways, each of the papers in this panel explores this liminal space of imagination and technology and demonstrates how this tension is productive for the study of how digital media are produced and used. This panel, in other words, takes as its starting point the double role of software in the social imagination: as a technical artifact it fulfills particular computational functions, yet software also serves as a powerful site through which stories are told about the meaning of technology and its relation to bodies, data, memory, knowledge, power, labor, and history. The first paper uses the contemporary turn to web nostalgia as a way to investigate the relationship between web archives, the popular imagination, and the construction of historical narratives. Exploring the history of the Internet Archive’s WayBack Machine as simultaneously a technical artifact, a trove for mining (algorithmically generated) images of the past, and a cultural reference to a subversive Cold War cartoon (“Peabody’s Improbable History), this paper considers how the discourse of “time travel” as historical method taps into desires for capturing and stabilizing an ephemeral past, thereby producing collective memory through a process of collaborative filtering. The second paper considers counting as a technology of the imagination, interrogating how today’s opportunities to self quantify are grounded in the longer history of counting in computing culture and also driven by an imagined future of digital self-actualization. This new iteration of what Weber calls the “spirit of calculation” materializes on the body through the connected technologies of activity tracking, productivity apps, and the aggregation of “body data”. The third paper traces the production of software from abstract concepts to concrete implementation by considering a key document in the software production process: the functional specification. This document, the paper argues, materializes software ahead of its materialization in code. The functional specification lays out software interfaces, functions, and use cases. To demonstrate the materiality of the functional specification, the paper presents a forbidden software system that never should be built. It thus uses one form of software materialization, the functional specification, as an imaginative thought experiment to stave off another materialization, the realization of software in code. The final paper asks how one technology may be imagined in another. It takes as its starting point the Perl programming language, which was considered crucial to web development in the 1990s but has arguably been superseded today. What is the status of Perl in web history, and how was it implicated in early imaginings of the web’s identity? The paper examines the histories of two Perl libraries, identifying a number of ways in which the language and its developers helped articulate the new medium.